Effects of Compressive and Tensile Strain on Macrophages during Simulated Orthodontic Tooth Movement. (28th April 2020) - Schröder, Agnes; Käppler, Paul; Nazet, Ute; Jantsch, Jonathan; Proff, Peter; Cieplik, Fabian; Deschner, James; Kirschneck, Christian
Abstract : During orthodontic tooth movement (OTM) to therapeutically correct the position of misaligned teeth, thus improving oral health and quality of life, fibroblasts, macrophages, and other immune cells within the periodontal ligament (PDL), which connects a tooth to its surrounding bone, are exposed to compressive and tensile strain. While it is known that PDL fibroblasts are critically involved in the biological regulation of OTM by a mechanotransductively triggered release of cytokines, it is unclear whether macrophages also react to pressure and tension in a similar manner thus impacting on or mediating OTM. RAW264.7 macrophages were seeded onto conventional 6-well cell culture plates for pressure or on Bioflex plates for tension assays and preincubated for 24 h. For in vitro simulation of physiological orthodontic compressive or tensile strain for 2 h, 4 h, 24 h, and 48 h, glass discs (2 g/cm 2 ) were placed or adherent macrophages isotropically stretched for 16%, respectively. We determined cell number, cytotoxicity, and gene/protein expression of Vegf-a /VEGF-A (macrophage-mediated angiogenesis), Mmp-8/9 (extracellular matrix reorganization), and Cox-2 /PG-E2, Il-6 /IL-6, and Tnf-α /TNF- α (proinflammatory mediators) by RT-qPCR and ELISA. Compressive but not tensile strain resulted in a significant reduction in cell number after only 2 h. Mmp-8 and Mmp-9 expression was significantly enhanced within 24 h of compressive and in part tensile strain. Significantly increased Vegf-a /VEGF-A expression was detected within 4 h of pressure, but not during application of tensile strain. Expression of proinflammatory mediators Cox-2 /PG-E2, Il-6 /IL-6, and Tnf-α /TNF- α was significantly increased as early as 2-4 h after application of compressive or tensile strain. Our results indicate that macrophages respond early on to compressive and tensile strain occurring during OTM with an enhanced gene expression of proinflammatory cytokines, which could affect PDL fibroblasts, osteoblasts, and immune cells triggering or enhancing the biological mechanisms and osteoclastogenesis underlying OTM.